Pengaruh Insentif Terhadap Produktivitas Kerja Karyawan Pada PT. Continental Tyre Indonesia - Rhoma Iskandar; Elysabet (Lembaga Pengembangan Kinerja Dosen, 2022)
Providing incentives to increase employee productivity at PT. Continental Tire Indonesia can be seen that: Incentives are given to employees every 6 months, the amount depends on the work performance that has been achieved by the employee concerned. From the data on the development of employee absenteeism and employee turnover (LTO) for 4 years, it can be seen that there is a decline. This reflects the reciprocal relationship between employees and the company that is created through the provision of incentives and welfare. Judging from the analysis of the company's development, there is an increase in employee work productivity from year to year. Work productivity from 2016 to 2019. From the results of the correlation analysis between incentive costs and business results obtained from the r-value of 0.2833, it can be seen that productivity increases. The results of the calculation of the coefficient of 1 determinant yield kp – 0.28. This means that the contribution of cash to increase in productivity is 38%. Provision of intensive employees at PT. CTI, can increase employee productivity itself, if intensive is good, it will increase employee productivity.